On the Symbolism of Rain in A Farewell to Arms - Mohammad Rahman (University of Chitral Journal of Linguistics and Literature, 2018)
This paper critically analyzes the symbolic use of rain in A Farewell to Arms (1929). The researcher has applied Sapir-Whorf Hypothesis as a research tool for the analysis of the text. This hypothesis argues that the languages spoken by a person determines how one observes this world and that the peculiarities encoded in each language are all different from one another. It affirms that speakers ofdifferent languages reflect the world in pretty different ways. Hemingway’s symbolic use of rain in A Farewell to Arms (1929) is denotative, connotative and ironical. The narrator and protagonist, Frederick Henry symbolically embodies his own perceptions about the world around him. He time and again talks about rain when something embarrassing is about to ensue like disease, injury, arrest, retreat,defeat, escape and even death. Secondly, Hemingway has connotatively used rain as a cleansing agent for washing the past memories out of his mind. Finally, the author has ironically used rain as a symbol when Henry insists on his love with Catherine Barkley while the latter being afraid of the rain, finds herself dead in it.